Case report: A case of ocular infection caused by Corynespora cassiicola - Wang, Qin; Wang, Lu; Lian, Lisha; Pu, Xiaofeng; Tang, Lu; Li, Yanmei; Liu, Yuan (Frontiers in Cellular and Infection Microbiology, 2023)
Objective: To identify the pathogen causing ocular infection in a Chinese patient and describe its morphological characteristics. Methods: Samples from the patient's intraoperative pus were collected for microscopic examination and culture. Morphology and drug sensitivities of the isolated fungus were analyzed. rDNA sequencing were performed and blasted in GenBank. Results: A strain of fungi was repeatedly isolated from pus samples in different types of mediums. No conidia were shown when the isolate cultured on normal PDA medium, while pseudoseptate thick-walled conidia showed when cultured on medium containing leaf leachate. The results of BLAST and phylogenetic trees based on internal transcribed spacer (ITS), beta-tubulin (BT2), translation elongation factor 1-alpha (tef-1) and RNA polymerase II (RPB2) gene demonstrated the isolated fungus was Corynespora cassiicola. Drug susceptibility test showed that this isolated Corynespora cassiicola was resistant or had relatively low susceptibility to 5-fluorocytosine, fluconazole and posaconazole, and sensitive to amphotericin B, anidulafungin, micafungin, caspofungin, voriconazole and itraconazole. Conclusion: The case was infected with Corynespora cassiicola and led to eye suppurative endophthalmitis and blindness. Combined applications of morphological and molecular biology techniques facilitate accurate diagnosis of fungal infections.